Comparison of single-phase transformerless photovoltaic grid-connected inverter topologies with high efficiency and low ground leakage current / Maaspaliza Azri - Maaspaliza, Azri (2014)
When a transformer is taken out of a photovoltaic (PV) inverter system, the efficiency of the whole system can be improved. Unfortunately, the additional ground leakage current appears and needs to be considered. The problem of ground leakage current is that it poses an electrical hazard to anyone touching the photovoltaic (PV) array’s surface. For safety issues, the ground leakage current should be less than 300 mA, which follows the VDE-0126-1-1 German standard. To minimize the ground leakage current in the transformerless PV grid connected inverter system, the proposed inverter topologies (SC-HB inverter, bipolar H-Bridge inverter with CD-Boost converter, modified unipolar H-Bridge inverter with CD-Boost converter and modified unipolar H-Bridge inverter with modified boost converter) are analyzed, verified and compared in this thesis. In order to analyze the effect of unbalanced filter inductance on the transformerless bipolar H-Bridge inverter topology, the matching ratio of inductance (Lr = Lf1/Lf1n and Lf2/Lf2n ) is investigated. In addition, the effect of parasitic capacitance value on the transformerless bipolar H-Bridge inverter topology is studied. The effect of modulation techniques using bipolar SPWM and unipolar SPWM on the transformerless H-Bridge inverter topology is compared and analyzed in terms of common-mode voltage and ground leakage current. TMS320F2812 is used as a controller to generate the PWM control signal, maximum power point tracking (MPPT) based on power balance and Proportional-Integral (PI) controller. PSIM 9.0 simulation software is used to design the proposed transformerless inverter topologies. Simulation and experimental results verified the proposed inverter’s feasibility in addressing issues of transformerless DC/AC converters in grid-connected PV systems.